2019
DOI: 10.1039/c9cc01145e
|View full text |Cite
|
Sign up to set email alerts
|

Visible responses under high pressure in crystals: phenolphthalein and its analogues with adjustable ring-opening threshold pressures

Abstract: Visible mechanochromism was triggered via the ring-opening reaction of phenolphthalein under high pressure. Different ring-opening threshold pressures and responsive colors were achieved by changing the substituent groups with different electronic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Differing from the anisotropic force during uniaxial compression, DAC techniques can provide isotropic stress and offer in situ absorption and fluorescence spectra, as well as micrographs visualizing the pressure-dependent mechanochromic behavior. While the pressure-induced ring-opening isomerization has been achieved in spiropyran crystals, 53 phenolphthalein/polymer blends, 54 and rhodamine/cyclodextrin complex, 55 the pressureinduced bond scission of the DDM structure has never been reported. Notably, new bands at ∼650 nm appeared and the intensity grew significantly in the UV−vis spectra of TGDDM-EDR-Rh-0% during compression by DACs (Figures 7b and S22), which suggested that similar green chromophores could also generate under hydrostatic pressure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Differing from the anisotropic force during uniaxial compression, DAC techniques can provide isotropic stress and offer in situ absorption and fluorescence spectra, as well as micrographs visualizing the pressure-dependent mechanochromic behavior. While the pressure-induced ring-opening isomerization has been achieved in spiropyran crystals, 53 phenolphthalein/polymer blends, 54 and rhodamine/cyclodextrin complex, 55 the pressureinduced bond scission of the DDM structure has never been reported. Notably, new bands at ∼650 nm appeared and the intensity grew significantly in the UV−vis spectra of TGDDM-EDR-Rh-0% during compression by DACs (Figures 7b and S22), which suggested that similar green chromophores could also generate under hydrostatic pressure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When the ground solid was fumed by THF, CH 2 Cl 2 , or chloroform, the fluorescence color recovered to green, and the fluorescence spectrum was also restored. Moreover, such color conversion could be repeated many times, suggesting a reversible process. Interestingly, yellow HBC-1 solids were sheared; the color changed into orange red, and the sheared section emitted weak red fluorescence under 365 nm light. After shearing for 4 min, almost all the solids emitted an orange-red fluorescence (Figure , right).…”
Section: Resultsmentioning
confidence: 99%
“…1,25–27 Under elevated pressures a decrease in the emissive response has traditionally been observed and attributed to an increase in π–π stacking interactions that leads to nonradiative decay. 27–33 Whereas an increase in the emissive response has been attributed to mechanisms such as RIR, RIM, the formation of exciton traps and an increase in radiative emission probabilities. 34–39 The emission spectrum is also affected under the application of pressure.…”
Section: Introductionmentioning
confidence: 99%